FDI, Economic Growth and Environmental Quality in the Nigerian Economy: New Evidences from System GMM - Hammed, Yinka Sabuur; Arawomo, Omosola (Journal of Economics and Behavioral Studies, 2022)
This paper examines the effect of foreign direct investment through economic activities on the environmental quality of the Nigerian economy by using annual data from 1981 to 2020. Our estimation of the simultaneous equation model was done through system GMM where we estimate the scale, technique and composition effects of foreign direct investment. Our results reveal that foreign direct investment improves economic activities through the scale effect and damages the environmental quality through technique and composition effects. The contribution of physical and human capital investment becomes more prominent in attracting direct investment inflow in the country. This however suggests that our institution should be strengthened to ensure the adoption of technology that poses little harm to the environment in the production process by the investors. Also, more investment should be made in physical and human capital in the country to attract more overseas investment.